SAMHD1 Phosphorylation at T592 Regulates Cellular Localization and S-phase Progression - Batalis, Stephanie; Rogers, LeAnn C.; Hemphill, Wayne O.; Mauney, Christopher H.; Ornelles, David A.; Hollis, Thomas (Frontiers in Molecular Biosciences, 2021)
SAMHD1 activity is regulated by a network of mechanisms including phosphorylation, oxidation, oligomerization, and others. Significant questions remain about the effects of phosphorylation on SAMHD1 function and activity. We investigated the effects of a SAMHD1 T592E phosphorylation mimic on its cellular localization, catalytic activity, and cell cycle progression. We found that the SAMHD1 T592E is a catalytically active enzyme that is inhibited by protein oxidation. SAMHD1 T592E is retained in the nucleus at higher levels than the wild-type protein during growth factor-mediated signaling. This nuclear localization protects SAMHD1 from oxidation by cytoplasmic ROS. The SAMHD1 T592E phosphomimetic further inhibits the cell cycle S/G2 transition. This has significant implications for SAMHD1 function in regulating innate immunity, antiviral response and DNA replication.